Penerapan Strategi Contextual Teaching and Learning (CTL) Untuk Meningkatkan Keaktifan dan Kooperatif Siswa Pada Pelajaran Pendidikan Agama Islam (Studi Kasus di SMP Negeri 2 Banyudono Tahun 2016/2017) - , Wahepi Suhartatik; , Drs. Zainal Abidin, M.Pd (2017)
School Based Curriculum (KTSP) is meaningless if the teacher‟s ability is inadequate of creating high quality learning. Learning quality depends on the teacher‟s skill, particularly in giving learning facility to the learners effectively and efficiently. CTL strategy is one of learning strategies which is hoped to be able to give learning process effectively. CTL focuses on the students activity from experience, not from knowledge which is transferred by teachers to the students. Through CTL, it is hoped to be able to give meaningful learning to the students. The main problems which are discussed in this study are as follows: (1) How the implementation of CTL strategy in the Islamic Education at Junior High School 2 Banyudono does; (2) What the student‟s attitudes are when joining teaching-learning of Islamic Education, The purposes of this study are as follows: (1) to know the implementation of CTL strategy; (2) to describe the student‟s attitude when joining teaching learning Islamic Education byusing CTL approach. This study uses a qualitative approach. The location of this research is at Junior High School 2 Banyudono. The object of this research are VIII grade students. The sequences of this research are observing the students and teacher while doing teaching learning in the class. Aspect of students being active are looked by observing the students while paying attention, answering the question, listening the explanation, and writing the materials from teacher. Meanwhile, student‟s cooperative aspectsare seen by listening teacher while explaining and writing the materials. Data are gained by observation, interview, and documentation which are processed by using triangulation to check the data validity. Analyzing the data is using interactive analysis. Based on the research can be concluded that: (1) CTL strategy in Islamic religious education has not been implemented by the teacher. Beside unfully implementation of CTL strategies, the students tend to be passive and quickly bored when learning takes place;(2) The problems of contextual study are as follows: the limitation of time schedule, facilities and teaching learning process are not good enough. The researcher gives suggestion related with contextual teaching learning in Junior High School 2 Banyudonoare as follows: (1) the teachers need to give exercise or seminar to make their quality better than before; (2) in the implementation of contextual teaching learning, teachers are hoped to be able to increase their quality by giving their learning experiences contextually to the students; (3) the facilities in the school should be increased in order to support the teaching learning process effectively and efficiently.